Studi Deskriptif Nilai Karakter Dongeng pada Buku Tematik Siswa Sekolah Dasar Kelas II Muatan Bahasa Indonesia Tema Kebersamaan - monyca Aprilia; resnani resnani; abdul muktadir (Universitas Bengkulu, 2022)
Character values are very important for the world of education to form good attitudes and behavior of students so that they have good actions. However, now there is a decrease in character values to students. Including, lack of interest in reading, lack of manners to old people, and lack of empathy towards fellow friends. Effort made to for the cultivation of character values occurs in the process of learning and habituation. The research about “a Descriptive Study of the Values of Fairy Tale Characters in the Thematic Book of Grade II Elementary School Students with Indonesian Language Theme Togetherness” is character value cultivation there are learning process, have a statement of problem about fairy tale character values contained in the thematic student book class II the theme of togetherness. The aims to desribe of analysis researh about caharacter value contained in fairy tale in the Thematic Book of Grade II Elementary School Students with Indonesian Language Theme Togetherness. In the thematic Book theme togetherness contained 9 stories there are, ingenuity breeds kindness, ducks always live in harmony, Kiki and Kiku, the friendship of an eagle and a rooster, the story of a cat and a mouse, a butterfly with a noble heart, an ant and a grasshopper, the origins of the city of surabaya, the friendship of an elephant and a mouse. This research used decriptive qualitative with subject research Fairy Tale Characters in the Thematic Book of Grade II Elementary School Students with Indonesian Language Theme Togetherness. Result of thid research about Fairy Tale Characters in the Thematic Book of Grade II Elementary School Students with Indonesian Language Theme Togetherness obtained as many as eleven character values there are, religious, honest, tolerant, disciplined, hard working, creative, independent, curiosity, love peace, social care and responsibility. The form of delivery of moral values that often appears directly is the form of delivery through characters.